Automation Work Order And Master Production Schedule In Enterprise Resources Planning For Pt Sfp - Nadia Revina Reka (IT for Society, 2023)
Abstract-In today's dynamic business landscape,manufacturing enterprises like PT SFP face the constantchallenge of optimizing their production processes to remaincompetitive. The Enterprise Resources Planning (ERP)architecture will be used to develop an integrated solution toautomate work order administration and master productionscheduling. The production and planning division is a veryimportant process and is interconnected with one another.Since manufacturing is the most demanding businessprocess in a company's activities, the significance of theplanning system is greatly raised. Even though the companyalready has an ERP system that is quite integrated, there arestill many processes that are still carried out offline whichcauses manual inefficiency, this not only increases waitingtime but can also cause anomalies. This project providesERP development ideas, especially in the Production andPlanning module for PT SFP by implementing automationand integration in the work order planning workflow toimprove business processes. It includes the business processof creating Order Confirmation (OC) Receiving Date Input,and automation of planning work order creation, usagestandards in the work order and the work order itself. Thissystem is expected to be more effective and efficient in the fieldof production planning using ERP web-based that can beaccessed online.